Coping with quarter-life crisis: An analysis of the role of social support and coping stress on senior university students - Dewi Ratnasari; Gisella Arnis Grafiyana; Nur’aeni Nur’aeni; Fatin Rohmah Nur Wahidah (Institut Agama Islam Negeri Langsa, 2023)
A quarter-life crisis is a phase in which individuals face a crisis in various aspects of life, such as prospects, romance, achievements, life goals, and careers. With appropriate support and the ability to manage stress, individuals can better confront challenges and succeed. This research aims to determine the influence of social support and stress coping on a quarter-life crisis. The study employs a quantitative approach with multiple linear regression analysis. The sample for this research consisted of 247 students, with 89 male and 158 female respondents aged between 21 and 25 years. The results of this research, based on data analysis at a significance level, indicate that for social support, the F-value is 36.598 with a p-value <.01, and social support has a 13% influence on the quarter-life crisis. For stress coping, the significance level yields an F-value of 93.425 with a p-value <.01, contributing to a 27.6% influence on the quarter-life crisis. Additionally, there is a significant influence between social support and stress coping on the quarter-life crisis, with an F-value of 54.992, p <.01 and R-squared .311, meaning that social support and stress coping together can contribute to a 31.1% influence on the quarter-life crisis. In conclusion, the presence or absence of social support and stress coping can affect the intensity of a quarter-life crisis.